Gestión pública y su incidencia en la calidad de los servicios del registro municipal de la propiedad y mercantil del cantón valencia, año 2023 - Nevárez Jiménez, Jefferson Hernán (2025)
This study focused on investigating the issue: how does Public Management impact the quality of services at the Municipal Property and Commercial Registry of the Valencia Canton in 2023? The main objective of this study was to evaluate Public Management in the quality of services at the Municipal Property and Commercial Registry of the Valencia Canton in 2023. The methodology included descriptive, quantitative, and qualitative research types. The methods used were analysis and synthesis, inductive reasoning, and documentary research. The population analyzed in this study included one registrar, five employees, and 51,509 users of the Municipal Property and Commercial Registry of the Valencia Canton. The sample was established by the entire registry staff, including the director and employees, while the users were calculated at a total of 381. The techniques used were interviews and surveys. The most relevant results show that, despite existing strengths and specific efforts to improve the services at the Municipal Property and Commercial Registry of the Valencia Canton, there are still significant challenges that require priority attention. The most relevant conclusions highlight significant deficiencies in the quality of the services offered, mainly related to the lack of technological modernization, inefficient administrative processes, limited staff training, and infrastructure deficiencies.